Mate attenuates DNA damage and carcinogenesis induced by diethylnitrosamine and thermal injury in rat esophagus - da Silva, Juliana Ferreira [UNESP]; Bidinotto, Lucas Tadeu [UNESP]; Furtado, Kelly Silva [UNESP]; Salvadori, Daisy Maria Favero [UNESP]; Rivelli, Diogo Pineda; de Morales Barros, Silvia Berlanga; Rodrigues, Maria Aparecida Marchesan [UNESP]; Barbisan, Luis Fernando [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
Drinking hot mate has been associated with risk for esophageal cancer in South America. Thus. the aims of this study were to evaluate the modifying effects of mate intake on DNA damage and esophageal carcinogenesis induced by diethylnitrosamine (DEN) and thermal injury (TI) in male Wistar rats. At the initiation phase of carcinogenesis, rats were treated with DEN (8 x 80 mg/kg) and submitted to TI (water at 65 degrees C, 1 ml/rat, instilled into the esophagus). Concomitantly, the animals received mate (2.0% w/v) for 8 weeks. Samples of peripheral blood were collected 4 h after the last DEN application for DNA damage analysis. At weeks 8 and 20, samples from esophagus and liver were also collected for histological and immunohistochemical analysis. Mate significantly decreased DNA damage in leukocytes, cell proliferation rates in both esophagus and liver and the number of preneoplastic liver lesions from DEN/TI-treated animals at week 8. A significant lower incidence of esophageal papillomas and liver adenomas and tumor multiplicity was observed in the animals previously treated with mate at week 20. Thus, mate presented protective effects against DNA damage and esophageal and liver carcinogenesis induced by DEN. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Mate; DNA damage; Diethylnitrosamine-induced esophageal and liver lesions